1998
DOI: 10.1002/1529-0131(199810)41:10<1867::aid-art20>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen replacement therapy and worsening of radiographic knee osteoarthritis: The Framingham study

Abstract: Objective.To examine whether estrogen replacement therapy (ERT) prevents worsening of radiographic knee osteoarthritis (OA) in elderly women.Methods. A total of 551 women ages 63-91 years (mean age 71) in the Framingham Study were followed up from biennial examination 18 (1983)(1984)(1985) to examination 22 (1992-1993). Data on postmenopausal ERT were obtained every 2 years. Subjects were classified into 3 groups according to their estrogen use at biennial examination 18: never users (n = 349), past users (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 3 publications
1
51
0
4
Order By: Relevance
“…Zhang et al (26) investigated the relationship between estrogen use and radiologic progression of knee OA. No significant association was found between current use, past use, or never use of estrogen and progression of knee OA.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al (26) investigated the relationship between estrogen use and radiologic progression of knee OA. No significant association was found between current use, past use, or never use of estrogen and progression of knee OA.…”
Section: Resultsmentioning
confidence: 99%
“…In a more clinically related study, Zhang et al demonstrated that postmenopausal women who take estrogen replacement therapy have a decreased chance of developing radiographic evidence of knee arthritis. In addition, the protective effect of estrogen replacement therapy was increased with the duration of the therapy [24]. It appears that estrogen may have a beneficial effect on cartilage; however, the exact mechanism of this protection has yet to be elucidated.…”
Section: Causes Of Knee Osteoarthritis In Womenmentioning
confidence: 99%
“…Estrogen replacement therapy (ERT) is effective in reducing or reversing postmenopausal bone loss [3] . In addition to its use for the treatment of postmenopausal symptoms, potential benefits of ERT include a reduction in the risk of osteoarthritis [4][5][6] and prevention of cardiovascular disease and dementia [7] . However, recent studies have shown that ERT is associated with a higher risk for breast, endometrial and ovarian cancer as well as cardiovascular disease and stroke [8,9] .…”
Section: Introductionmentioning
confidence: 99%